1981
DOI: 10.1007/bf00008266
|View full text |Cite
|
Sign up to set email alerts
|

Metal concentrations in certain coastal organisms from Beirut

Abstract: Trace metal concentrations were determined in six species of intertidal organisms common to the coast of Ras Beirut, Lebanon . Lead, cadmium, nickel, iron, and zinc were highest in the polychaete, Hermodice carunculata, but the eggs of the sea urchin, Arbacia lixula, had similar iron levels and the sea anemone, Actinia equina, had zinc concentrations which also approached levels in the polychaete . The highest copper occurred in the shore crab, Pachygrapsus transversus, while chromium was highest in the eggs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The concentration of heavy metals in bivalve molluscs from marine environments of different geographical regions . However, copper concentrations were considerably (a factor 2 to 8) lower than in crab species from contaminated coastal environments from temperate (Stenner & Nickless, 1974 ;Lande, 1977 ;Karbe et al, 1988) and subtropical latitudes (Stenner & Nickless, 1975 ;Cuadras et al, 1981 ;Shiber, 1981). However, copper concentrations were considerably (a factor 2 to 8) lower than in crab species from contaminated coastal environments from temperate (Stenner & Nickless, 1974 ;Lande, 1977 ;Karbe et al, 1988) and subtropical latitudes (Stenner & Nickless, 1975 ;Cuadras et al, 1981 ;Shiber, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…The concentration of heavy metals in bivalve molluscs from marine environments of different geographical regions . However, copper concentrations were considerably (a factor 2 to 8) lower than in crab species from contaminated coastal environments from temperate (Stenner & Nickless, 1974 ;Lande, 1977 ;Karbe et al, 1988) and subtropical latitudes (Stenner & Nickless, 1975 ;Cuadras et al, 1981 ;Shiber, 1981). However, copper concentrations were considerably (a factor 2 to 8) lower than in crab species from contaminated coastal environments from temperate (Stenner & Nickless, 1974 ;Lande, 1977 ;Karbe et al, 1988) and subtropical latitudes (Stenner & Nickless, 1975 ;Cuadras et al, 1981 ;Shiber, 1981).…”
Section: Discussionmentioning
confidence: 97%
“…amphipods, polychaetes, chaetognaths, jellyfish, etc.). The Fe content for this functional group (0.0254-0.0697 kg Fe t −1 wet weight) is an average of the low and high Fe estimates for amphipods (0.00559-0.1035 kg Fe t −1 wet weight [67][68][69], using a 23 : 100 dry : wet weight ratio [70]); chaetognaths (0.01767 kg Fe t −1 wet weight [68], using a 9.3 : 100 dry : wet weight ratio [70]; and jellyfish (0.053-0.088 kg Fe t −1 wet weight [71], as reported in Moreno & Haffa ([66], table 1).…”
Section: (B) Taxonomic Composition and Fe Content Of Functional Groupsmentioning
confidence: 99%
“…Marine specimens collected from industrial areas often have slightly higher burdens than those found in freshwater Toxicity 69 species. Residues in wrass from the Mediterranean (Lebanon) reached 1.6 mg kg-' wet weight whereas several species collected from the coast ofIsrael had up to 1 mg Cr kg-' (Shiber, 1981;. There are numerous reports from other industrialized areas indicating residues in muscle do not exceed 0.5 mg kg-I.…”
Section: Aquatic Plants Invertebrates and Fishmentioning
confidence: 99%
“…Similarly, maximum levels in molluscs and crustaceans collected near Sudbury were 29 -39 mg kg-I wet weight (Hutchinson et al, 1975). Mediterranean coastal waters (Lebanon) yielded molluscs, polychaetes, urchins, and anemones containing soft tissue residues of < 0.1-40 mg kg-I wet weight (Shiber, 1981) though levels in the bivalve Scrobicularia plana inhabiting unpolluted English waters reached 11.9 mg kg-I dry weight (Bryan and Hummerstone, 1978). Several other gastropod and bivalve species, collected from various unpolluted and polluted sites throughout the world, carried residues of 0.3-<9.5 mg kg-I dry weight (Karbe et aI., 1977;Watling and Watling, 1976).…”
Section: Invertebratesmentioning
confidence: 99%